Evaluasi Interval Penggantian Preventif pada Komponen Kritis Screw Conditioner - Adib, Adib; Pandria, T.M Azis; Hartati, Rita (Universitas Teuku Umar, 2020)
This research is propose the replacement schedule of a critical part of a critical machine in a the clove line of PT. Hanjaya Mandala Sampoerna Tbk. From the direct observation, the screw conditioning process is the critical process of the the tobacco production in clove line. One of the screw conditioner, Garbuio Dickinson screw conditioner, was observed as the machine with the most downtime in clove line. Further analysis using chart reveals that the motor screw conditioner is the main problem to the machine breakdown. Index of fit calculations were applied to find the time to failure and time to repair distribution by looking at the highest index of fit of each failure distribution. Maximum Likelihood Estimator step was undergone to find the MTTF and MTTR (in hours) for the chosen distribution. Finally, the best time interval to replace the critical part in order to increase the component reliability and machine availability was calculated. Result of this preventive replacement is increases the component reliability by 80% and the machine availability by 0.245%.